2020
DOI: 10.1007/s11896-020-09397-9
|View full text |Cite
|
Sign up to set email alerts
|

I’m Still in the Blue Family: Gender and Professional Identity Construction in Police Officers

Abstract: With an increase in gender equality policies and gender balance targets within traditionally male professions, organisations such as the police service are experiencing changing demographics. How these shifts influence the construction of professional identity is unclear. Drawing on focus group data, this study aimed to explore identity construction of police officers across gender using a thematic analysis method. Two themes related to identity construction were found to be common to both male and female poli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Much of the research available on policing has utilized the narrative of the ‘family’–e.g., “Blue Family” ( du Pleissis et al, 2020 ) and “Brotherhood” ( Campeau, 2019 )–to refer to a ‘sense of belonging and service as a family’ that distinguishes policing from other realms of work ( du Pleissis et al, 2020 , p. 5). This is also the case with the women we spoke with.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of the research available on policing has utilized the narrative of the ‘family’–e.g., “Blue Family” ( du Pleissis et al, 2020 ) and “Brotherhood” ( Campeau, 2019 )–to refer to a ‘sense of belonging and service as a family’ that distinguishes policing from other realms of work ( du Pleissis et al, 2020 , p. 5). This is also the case with the women we spoke with.…”
Section: Methodsmentioning
confidence: 99%
“…Brotherhood is a prominent narrative in policing likening it to familial bonds (see du Pleissis et al, 2020 ). And, like many families, the Brother hood is rife with gender dynamics that shape experiences and inequities.…”
Section: Gender Culture Policing and Fit: A Review Of The Literaturementioning
confidence: 99%
“…This latest revelation appears to challenge prevailing views of the police force as monolithic and negative (Cordner, 2017; Reiner, 2017). The inclusion of a range of people from different walks of life showed that the NZ Police demonstrate what du Plessis et al, (2021, p. 388), have concluded about other police forces globally and that is ‘…individuals may hold a common strong shared identity of a police officer, but simultaneously hold different and sometimes competing values as to what that looks like in behavioural action.’ The diversity and willingness to embrace personal identities while on the job also aligns with Cordner’s (2017, p. 21) assessment that ‘…variations in officers’ outlooks tend to be associated more strongly with the particular police organization for which they work than with their personal characteristics.’…”
Section: Discussionmentioning
confidence: 89%
“…The police force is a 'masculine frontier' and working as a police officer is an occupation that confers masculine identity (Aiello, 2014). Being a police officer is understood as an enduring identity (du Plessis et al, 2021). From a historical perspective, Barrie and Broomhall (2012) argue that policing offers a case study in how masculinity has been constructed and applied over the last three hundred years.…”
Section: Policing Culturementioning
confidence: 99%